"Is He Talking to Me?": How Breaking the Fourth Wall Influences Enjoyment. Issue 2 (1st June 2020) - Schlütz, Daniela M.; Possler, Daniel; Golombek, Lucas
Abstract: In this study, we empirically investigate the enjoyment-related consequences of the TV trope of breaking the fourth wall (B4W), which is when a fictional character addresses viewers directly. Based on the model of narrative comprehension and engagement, we assume that B4W contributes to viewers' cognitive and affective enjoyment by intensifying the parasocial interaction experience (EPSI). Alternatively, B4W could reduce enjoyment by disrupting viewers' transportation into the narrative. We report two experiments with a total of N = 658 participants and three different stimuli based on the TV series House of Cards ( HoC ) and Malcolm in the Middle ( MitM ) as well as the movie Deadpool ( DP ). Analyses revealed that B4W increased the EPSI, which in turn fostered enjoyment.